Peirce’s open community in light of sentimentalism and normative sciences - Flórez, Jorge Alejandro; Acosta López de Mesa, Juliana (Estudios de Filosofía, 2022)
Peirce’s idea of an unlimited community has been usually analyzed from its role in science and the normative ideal of truth. However, it is essential to understand the role of the community of inquiry in light of the other normative sciences, aesthetics and ethics, since according to Peirce, any endeavor to know that is not guided by the esthetical ideal of admirable per se should not be considered as proper science, but as a power tool to benefit some elite. This article aims to analyze Peirce’s idea of community of inquiry in light of sentimentalism and the normative sciences in order to evidence that such community is not elitist, but open, insofar as it is also lured by the summum bonum and the admirable per se. Finally, we provide a more organic reading of Peirce’s work, opening the way to consider possible consequences of this position from an ethical and political perspective.